Community Participation in Decision Making Processes in Urban Planning: The Case of Kaunas - Laura Jankauskaite-Jureviciene; Aušra Mlinkauskienė (Journal of Contemporary Urban Affairs, 2021)
Participation in decision-making processes foreshadows enabling citizens, communities, non-governmental organizations and other interested parties to influence the formulation of policies and laws affecting them.  The purpose of this study is not only to review Lithuanian legal documents but also to analyse recent processes in Kaunas city planning. Kaunas city is undergoing various urban processes, which do not always meet the needs of the community. This study presents an analysis of the forms of community involvement in the urban planning processes and survey data on the effectiveness of community involvement. The methodology requires using a sociological survey with representatives of the city community and a comparative analysis between legal obligations and actual urbanization process.